2002 год. Весенняя сессия, 16 янв. - 8 февр. - Теплова М. О. (2004)
Экземпляры: КХ (20060121) / Инвентарный номер: 1054770 / Цена: 20.00 / Сис.шифр: 67.400 / Авт.знак: Г 72 / ГРНТИ: 10 / ББК: 67.400.621